2005
DOI: 10.1530/eje.1.01964
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone substitution with a new transdermal, hydroalcoholic gel applied to scrotal or non-scrotal skin: a multicentre trial

Abstract: Objective: Testosterone-containing gels have improved testosterone substitution therapy, but they are associated with the risk of interpersonal transfer. Therefore, we tested a new hydroalcoholic 2.5% testosterone gel (TGW), which was removed by washing 10 min after administration. Design: The gel was applied to scrotal or non-scrotal skin in comparison to two 2.5 mg Androderm w patches in a randomised, three-arm, parallel-group, controlled multicentre trial over a period of 24 weeks. We included symptomatic h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 15 publications
0
28
0
Order By: Relevance
“…285,286 In addition, no effect was found of testosterone replacement therapy on PSA levels [287][288][289] and the change in PSA were not influenced by the mode of testosterone replacement therapy, patient age, or baseline levels of PSA or testosterone. 290 The online prostate cancer risk calculator is one of the most commonly used tools to assist the clinician in assessing the risk of prostate cancer. [291][292][293] All men who present for TRT should undergo prostate biopsy if they have abnormal PSA level or abnormal result on digital rectal examination with low threshold to do or repeat prostate biopsy if the PSA level or digital rectal exam changes.…”
Section: Prostate Cancermentioning
confidence: 99%
“…285,286 In addition, no effect was found of testosterone replacement therapy on PSA levels [287][288][289] and the change in PSA were not influenced by the mode of testosterone replacement therapy, patient age, or baseline levels of PSA or testosterone. 290 The online prostate cancer risk calculator is one of the most commonly used tools to assist the clinician in assessing the risk of prostate cancer. [291][292][293] All men who present for TRT should undergo prostate biopsy if they have abnormal PSA level or abnormal result on digital rectal examination with low threshold to do or repeat prostate biopsy if the PSA level or digital rectal exam changes.…”
Section: Prostate Cancermentioning
confidence: 99%
“…30 In a short-term study with Testim, Loizides and colleagues 54 showed that measures of positive and negative mood improved significantly, beginning with the first week of therapy and reaching a maximal response at the second week. Kuhnert and colleagues 28 have reported similar findings.…”
Section: Dovepressmentioning
confidence: 63%
“…The dose-dependent improvements in all pharmacokinetic profiles of testosterone gel in comparison to testosterone patch have been replicated in other studies. [28][29][30][31] In a open-label crossover study of 30 hypogonadal men with human immunodeficiency virus (HIV), Scott and colleagues 32 compared the response between weekly intramuscular (IM) testosterone (100-200 mg/week) and 1% Androgel (5-10 g/day) for eight weeks. Peak levels of serum-free testosterone concentrations were significantly greater after IM testosterone (42 pg/mL) than after Androgel (23 pg/mL) (P  0.001).…”
Section: Dovepressmentioning
confidence: 99%
See 1 more Smart Citation
“…39 Transdermal patches usually deliver 5-6 mg of T daily and provide relatively steady state T levels at low to midnormal ranges. 13,15,16,31,40,60,61,88 Higher T level can be achieved by applying more than one transdermal patch. Long term use of patches for 3-10 years has been shown to be effective in maintaining SF, bone density and muscle mass in both young and elderly hypogonadal men.…”
Section: Testosterone Application (Gels/patches)mentioning
confidence: 99%